2020
DOI: 10.3390/oceans1030012
|View full text |Cite
|
Sign up to set email alerts
|

Oceanographic Determinants of the Abundance of Common Dolphins (Delphinus delphis) in the South of Portugal

Abstract: Off mainland Portugal, the common dolphin (Delphinus delphis) is the most sighted cetacean, although information on this species is limited. The Atlantic coast of Southern Portugal is characterized by an intense wind-driven upwelling, creating ideal conditions for common dolphins. Using data collected aboard whale-watching boats (1929 sightings and 4548 h effort during 2010–2014), this study aims to understand the relationships between abundance rates (AR) of dolphins of different age classes (adults, juvenile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…A radio antenna system installed on the UAV allowed live-streaming of video during flight. The study site was located in the Algarve region in the south coast of Portugal, between Cape St. Vicente (37 • [24,25]. It is also a region where both dolphin species are the focus of commercial whale-watching tours [26,27].…”
Section: Methodsmentioning
confidence: 99%
“…A radio antenna system installed on the UAV allowed live-streaming of video during flight. The study site was located in the Algarve region in the south coast of Portugal, between Cape St. Vicente (37 • [24,25]. It is also a region where both dolphin species are the focus of commercial whale-watching tours [26,27].…”
Section: Methodsmentioning
confidence: 99%
“…Second, it is difficult to estimate the number of individuals of large groups of dolphins-mainly Delphinus delphis and Tursiops truncatus off the Algarve. In this region, groups of Delphinus delphis, including newborns and calves, can reach up to 1,000 individuals and averaging 31.0 ± 51.6 individuals (Moura et al, 2012;Castro et al, 2020), however, the average of the minimum number of individuals we retrieved from social media was two times lower-14.1 ± 53.5 individuals. This is less problematic for most species because they were present in small groups, or the posts often mentioned the number of individuals observed.…”
Section: Advantages and Disadvantages Of Iecology To Study Cetaceansmentioning
confidence: 85%
“…One study registered the presence of six species along a ∼30 km coast stretch in the western Algarve during a little over 8 months (Castro, 2010), while the other study reported the presence of 11 species along the entire region during 6-month periods over 10 years (Laborde et al, 2019). Existing knowledge is mostly published as gray literature, while peer-reviewed publications are scarce and have focused on strandings (Silva and Sequeira, 2003;Sousa and Brito, 2012), aspects of population connectivity (Alves et al, 2019;Dinis et al, 2021) the population ecology of Delphinus delphis (Moura et al, 2012;Castro et al, 2020), and Orcinus orca (Esteban et al, 2013) description of opportunistic observations (Martin and Walker, 1997;Báez et al, 2007), interaction with fisheries (Goetz et al, 2015;Marçalo et al, 2015), diet (Marçalo et al, 2018(Marçalo et al, , 2021 or diet/trophic ecology (Giménez et al, 2017), behavioral responses to drones (Castro et al, 2021), and epidemiology (Bento et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of Mysticeti in coastal waters of mainland Portugal is usually limited to rare encounters, except for minke whales (B. acutorostrata) that occur regularly (Bencatel et al, 2017). The south coast of Portugal is characterised by an intense wind-driven upwelling season from March to October and an upwelling system in the area of Cape St. Vincent (García Lafuente and Ruiz, 2007) making this an important region for cetaceans (Castro et al, 2020;Moura et al, 2012). During the summer months of 2020, the number of sightings of baleen whales along the south coast of Portugal was the highest in the past five years (22 sightings compared with an average of 10 sightings per year), with the majority of the sighted animals identified as minke whales (AIMM, unpublished data).…”
mentioning
confidence: 99%
“…This sighting represents a new record for Bryde's whale in mainland Portugal. The south of Portugal is an important region supporting considerable biodiversity (Lopes and Cunha, 2010) but only limited dedicated cetacean studies and surveys have taken place here because of financial and time constraints and the personnel required (Castro et al, 2020). It is essential to develop more scientific surveys in the region in order to have a better understanding of the cetacean diversity in the area.…”
mentioning
confidence: 99%